2022
DOI: 10.24002/konstelasi.v2i1.5545
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Green Human Resource Management Terhadap Peningkatan Kepuasan Kerja dan Produktivitas Karyawan Melalui Perspektif Technology Acceptance Model (TAM)

Abstract: Konsep Manajemen Sumber Daya Manusia (MSDM) saat ini telah berkembang bila selama ini terdapat anggapan bahwa proses MSDM sering berhubungan dengan pemakaian bahan yang sangat banyak seperti kertas, alat tulis dan sebagainya. Saat ini dikenal konsep green human resource management (GHRM), konsep ini memberikan solusi bagaimana mengimplementasikan pengelolaan sumber daya manusia dengan meninimalkan penggunaan bahan perkantoran. Solusinya adalah dengan memanfaatkan teknologi seperti aplikasi ataupun platform dig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
1
0
0
Order By: Relevance
“…The findings of this study thus concur with those of research (Wijonarko & Wirapraja, 2022), which found that green culture is a critical element in boosting worker productivity. The study's findings indicate that the company would be wise to adopt a "green culture," as it can assist businesses in adhering to environmental laws and regulations while lowering their risk of facing legal repercussions and reputational harm.…”
Section: The Effect Of Adaption Of Green Culture On Work Productivitysupporting
confidence: 90%
“…The findings of this study thus concur with those of research (Wijonarko & Wirapraja, 2022), which found that green culture is a critical element in boosting worker productivity. The study's findings indicate that the company would be wise to adopt a "green culture," as it can assist businesses in adhering to environmental laws and regulations while lowering their risk of facing legal repercussions and reputational harm.…”
Section: The Effect Of Adaption Of Green Culture On Work Productivitysupporting
confidence: 90%